IMPLEMENTATION OF ARTICLE 201 PARAGRAPH (11) OF THE LAW OF THE REPUBLIC OF INDONESIA NUMBER 6 OF 2020 (STUDY OF PENJABAT MAYOR OF PEKANBARU) - Afrinaldy Rustam; Sabarno Dwirianto (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
This research wasbased on the occurrence of a public pegantian penjabat event in Kota Pekanbaru Riau Province. The change was made for a period of two years to fill the vacancy in the position of Mayor of Pekanbaru. This type of research is normative legal research. The data collection method used in this study is by conducting a literature study related to the object of this study. Data analysis in this study was carried out systematically based on research problems that were described qualitatively. The results in this study show that the change of Mayor of Pekanbaru must be in accordance with the established legal umbrella. Whoever the person is, the acting Mayor of Pekanbaru must put the interests of the general public first. Then, the public official fulfills the rank and position and must be proposed by the governor as a higher official. The results obtained turned out that the acting Mayor of Pekanbaru was the choice of the Ministry of Home Affairs based on the results of the proposal of the confidant of the Minister of Home Affairs who came from a social organization. It is unfortunate because it will be questioned about the credibility, professionalism, and accessibility of the sworn officials. Therefore, the acting Mayor of Pekanbaru is inseparable from political interests where these political interests are inseparable from the fight between the elite in the capital of Riau Province and the elite in the National Capital, Jakarta.